DESIGN AND CONSTRUCTION OF SPICE SHIPER AND DRYER (FIVING) WITH FUZZY LOGIC CONTROL APPROACH - Faikul Umam; Firmansyah Adi Putra; Hanifudin Sukri (International Journal of Science, Engineering, and Information Technology, 2021)
One sector that needs to be researched intensively and comprehensively is the food sector (Spices). Spices (Temu-finding) or known as ginger plants are plants that are used as basic ingredients for traditional medicine or herbal medicine.problems faced by traditional herbal medicine farmers, including spice processing technology is still not there. This is evidenced that the processing of spices into traditional herbal medicine is done manually. The problem in the initial process of drying the basic ingredients of Madurese traditional herbal medicine, requires a relatively long time so that the productivity of Madurese traditional herbs can only be produced in a limited manner depending on the weather. Another problem is that human resources are still in the traditional paradigm, meaning they still believe that traditional herbal medicine processing is more efficacious than using processed using technology.The purpose of this research is to develop this technology designed to increase the productivity of traditional herbal medicine production in Madura so that it has high quality and competitiveness. On the other hand, increasing the productivity of traditional herbal medicine production will have a positive impact on spice farmers (findings) in the form of increasing the economic level of farmers and traditional herbal medicine entrepreneurs. It is hoped that this research can provide technological solutions to spice farmers and traditional herbal medicine entrepreneurs in Madura as well as increase the productivity of Madurese traditional herbs and spices.